Teaching english to children from 5 to 7 years old through fair tales - Merizalde, Nathaly (2013)
Fairy Tales are the best known, most beloved and influential genres of literature which at the very beginning of History was told orally. We can define this kind of tales as stories of enchantment, legendary deeds and creatures. The Fairy tales are one of the most important genres of literature that is well recognized, so this kind of genre of literature is the favorite for most people and passed from generation to generation through oral storytelling. These Tales are considered stories of fantasy. They are stories for children often they have imaginary creatures and wonderful adventures. Fairy tales are funny, fantastic, and colorful. Also, they have an important role in children s imagination. This project is about the Fairy Tales as a methodological resource in the class. They are considered a methodological resource since they help to capture the attention of the students in the classroom, especially in young children. Through this technique students can be interested in learning English.